Spies in disguise [videorecording (Blu-Ray + DVD)] - Hewitt, Cindy Davis; Copeland, Brad; Taylor, Lloyd (Screenwriter); Mendelsohn, Ben; Gillan, Karen, 1987-; Shapiro, Theodore, 1971-; Martell, Lucas (20th Century Fox Home Entertainment, 2020)
After secret agent Lance Sterling is accidentally transformed into a pigeon by intelligent young scientist Walter Beckett, the two must work together to stop a revenge-seeking cybernetic terrorist and return the agent to his human form.